Energy-Efficient Routing Protocol Based on Zone for Heterogeneous Wireless Sensor Networks - Jia Yanfei; Chen Guangda; Zhao Liquan (Journal of Electrical and Computer Engineering)
In heterogeneous wireless sensor networks, sensor nodes are randomly distributed in some regions. In some applications, they may be randomly distributed in different regions. Besides, nodes with the same type have almost the same probability to be selected as cluster head. The cluster head will consume much more energy to receive and transmit data than the other nodes. If nodes with little residual energy have been elected as cluster heads, it will affect the efficiency of the network due to its early death. An improved energy-efficient routing protocol is proposed for heterogeneous wireless sensor networks. Firstly, it supposes that the different types of nodes are distributed in different zones. Secondly, by improving the threshold, nodes with large residual energy have a greater possibility of becoming cluster heads. In the end, it designs a mixed data transmission method. The cluster heads of supper nodes and advance nodes directly transmit data to the base station. The normal nodes adopt single hops and multiple hops mixed methods to transmit data. This can minimize the energy of the communication from cluster head to base station. Simulation results show that this algorithm has achieved a longer lifetime for the wireless sensor network than stable election protocol and threshold-sensitive stable election protocol algorithm.